La gloria y el concepto de los político en Giorgio Agamben. - Alfonso Galindo Hervás. (Revista de Estudios Sociales, 2010)
This article analyzes the concept of the political proposed by Giorgio Agamben in a genealogical study of the concepts of government and glory. To this end, it criticizes Agamben’s proposal on two counts: its relevance from the perspective of conceptual history; and its deficiencies in terms philosophies, such as Hans Blumenberg’s, that underline the importance of myths as a source of meaning and an indication of the human determination to survive.